Sikap dan Preferensi Konsumen Terhadap Kopi Arabika Gayo - Nurul A'la; Rita Nurmalina; Suprehatin Suprehatin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2024)
The research aims to identify purchasing decisions, as well as to analyze consumer attitudes and preferences towards Gayo Arabica Coffee. This research uses primary data from an online survey using google forms involving 223 respondents who participated. Data were analyzed using descriptive analysis, fishbein multi-attribute analysis, and conjoint analysis. The research results show that the consumer decision making process goes through five decision stages. The comparison between three variants of arabica coffee, namely Gayo Arabica Coffee, Sidikalang Coffee, and Mandheling (lintong) Coffee show that consumer attitudes towards Gayo Arabica Coffee are more positive by 170.16 points. Gayo Arabica Coffee has advantages in the attributes of taste, aroma, product availability, aftertaste, and product information. This is supported by the results of consumer preferences on the level of attribute importance; the taste attribute has the highest level of attribute importance in Gayo Arabica Coffee products at 30.79 percent. Consumers also prefer Gayo Arabica Coffee, which has a sweet taste, a lingering aftertaste, strong aroma, light viscosity and a price of Rp 35,000/250g. Therefore, producers need to make improvements to product attributes that do not meet consumer expectations, as well as improve and maintain product attributes that meet consumer expectations.